Lesson Learned from General Soedirman’s Leadership Pattern in Guerrilla Warfare - Tara, Kadek Deddy; Sumertha, I Gede; Tirto, Djayeng; Sukendro, Achmed; Widodo, Pujo (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to find out the background of General Soedirman, who was an Independence Fighter during the Revolutionary Period in his position as the first Commander-in-Chief General of Indonesia. In his struggle to obtain Indonesian Independence, he went through a long series of struggles through the Guerrilla War. This research method uses heuristical stages, source criticism, interpretation, and historiography. The results of this research show the biography of General Soedirman and his struggle to achieve Indonesian independence through the Guerrilla War method used against the Dutch to fight for Indonesian independence. Emphasized his heroic and patriotic actions. The proclamation of Indonesian independence which was announced on August 17, 1945, inspired the leaders and the entire Indonesian nation to start fighting hard to maintain that independence. Great General Soedirman was a hero who fought to win the independence of the Republic of Indonesia from the hands of colonialism. General Soedirman fought for Indonesia's independence despite the shortcomings of his troops and weakening health, but his love for the independent Indonesian nation fueled his enthusiasm to continue fighting under any circumstances. His personality is firm in his principles and beliefs, always prioritizing the interests of the community and the nation above his interests. In the history of the struggle of the Republic of Indonesia, he is recorded as the first and youngest Commander and General of the Republic of Indonesia.